Requirements for essential micronutrients during caloric restriction and fasting - Zhang, Weiguo; Chen, Peng; Huo, Shaofeng; Huang, Xiaomin; Zhao, Youyou (Frontiers in Nutrition, 2024)
Caloric restriction (CR) or energy restriction, when carefully designed, monitored, and implemented in self-motivated and compliant individuals, proves to be a viable nonpharmacologic strategy for human weight control and obesity management. Beyond its role in weight management, CR has the potential to impede responses involved not only in the pathogenesis of various diseases but also in the aging process in adults, thereby being proposed to promote a healthier and longer life. The core objective of implementing caloric restriction is to establish a balance between energy intake and expenditure, typically involving a reduction in intake and an increase in expenditure -a negative balance at least initially. It may transition towards and maintain a more desired equilibrium over time. However, it is essential to note that CR may lead to a proportional reduction in micronutrient intake unless corresponding supplementation is provided. Historical human case reports on CR have consistently maintained adequate intakes (AI) or recommended dietary allowances (RDA) for essential micronutrients, including vitamins and minerals. Similarly, longevity studies involving non-human primates have upheld micronutrient consumption levels comparable to control groups or baseline measures. Recent randomized controlled trials (RCTs) have also endorsed daily supplementation of multivitamins and minerals to meet micronutrient needs. However, aside from these human case reports, limited human trials, and primate experiments, there remains a notable gap in human research specifically addressing precise micronutrient requirements during CR. While adhering to AI or RDA for minerals and vitamins appears sensible in the current practice, it's important to recognize that these guidelines are formulated for generally healthy populations under standard circumstances. The adequacy of these guidelines in the setting of prolonged and profound negative energy balance remains unclear. From perspectives of evidence-based medicine and precision nutrition, this field necessitates comprehensive exploration to uncover the intricacies of absorption, utilization, metabolism, and requirement of each hydrophilic and lipophilic vitamin, and mineral during these special periods. Such investigations are crucial to determine whether existing daily dietary recommendations for micronutrients are quantitatively inadequate, excessive, or appropriate when energy balance remains negative over extended durations.